2019
DOI: 10.1002/smll.201905081
|View full text |Cite
|
Sign up to set email alerts
|

Nonconfinement Structure Revealed in Dion–Jacobson Type Quasi‐2D Perovskite Expedites Interlayer Charge Transport

Abstract: n-layered corner-sharing [BX 6 ] 4− octahedra separated by L, where n denotes the theoretical thickness of perovskite phase. [5] The L cation acts to improve both self-assembly capability and hydrophobicity of perovskite materials. [6,7] However, the poor interlayer charge carrier transport of 2D RP halide perovskites, which is attributed to the thick double insulating L layers, remains an open issue and invokes intense investigation.In general, the photogenerated excitons in 2D perovskites likely fall betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 26 publications
2
79
0
Order By: Relevance
“…[ 49 ] Here our results indicate that ion migration can still be efficiently suppressed in DJ perovskites, despite the much shorter interlayer spacing in PPD‐based DJ perovskite (4.66 Å) [ 50 ] (see Supporting Information, Figure S11 and Note 2) and PXD‐based DJ perovskite (6.74 Å). [ 51 ] On the other hand, this result also indicates an ignorable contribution to ion conductivity by the possible MAPbI 3 phase. The negligible hysteresis in J–V curves between reverse and forward scan (Figure 3b) also support the ignorable trends of ion migration in the DJ PSCs.…”
Section: Resultsmentioning
confidence: 86%
“…[ 49 ] Here our results indicate that ion migration can still be efficiently suppressed in DJ perovskites, despite the much shorter interlayer spacing in PPD‐based DJ perovskite (4.66 Å) [ 50 ] (see Supporting Information, Figure S11 and Note 2) and PXD‐based DJ perovskite (6.74 Å). [ 51 ] On the other hand, this result also indicates an ignorable contribution to ion conductivity by the possible MAPbI 3 phase. The negligible hysteresis in J–V curves between reverse and forward scan (Figure 3b) also support the ignorable trends of ion migration in the DJ PSCs.…”
Section: Resultsmentioning
confidence: 86%
“… 69 Consequently, the nonconfinement structure displayed E b of ∼69 meV which expedite exciton dissociation and interlayer charge transport. 69 This is in agreement with recent DFT calculation on ethylenediamine cation (EDE)-based 2D DJ perovskites, whereby n ≥ 3 samples offered enhanced stability, smaller effective masses, larger dielectric constants, and lower E b in comparison to their conventional 3D counterpart. 73 In fact, E b of (EDA)Cs n –1 Pb n I 3 n +1 perovskites ( n ≥ 3) falls between 29 and 46 meV, and their enhanced stability is related to the strong I–H interaction of diamine cations with a shortened interlayer distance of ∼3.5 Å.…”
mentioning
confidence: 99%
“…[35,246] An even smaller interlayer distance of 3.36 Å is obtained for the for n > 3 LPKs based on PDMA. [57] Hall effect measurements show p-type behavior with a carrier concentration of 3.00 × 10 8 cm -3 and Hall mobility of 0.75 cm 2 V -1 s -1 for n = 10, comparable to 3D perovskites. [247] The determined electron diffusion length of 800 nm, using intensitymodulated photocurrent spectroscopy and intensity-modulated photovoltage spectroscopy, is again very similar to the 3D counterpart.…”
Section: (18 Of 26)mentioning
confidence: 74%
“…[60,61] For example, the small DJ-spacer p-xylylenediamine (PDMA) was shown to lead to non-confined structures at n > 3 with an interlayer distance of only 3.4 Å (Figure 4a). [57] This results in a reduced bandgap below 1.7 eV and lowered exciton binding energy down to 69 meV corresponding to a free charge carrier to exciton ratio of 97.9% under operating photovoltaic conditions. However, at larger d-spacings above 20 Å, systematic experimental and theoretical studies on aliphatic spacers have found the bandgap (2.7 eV) and exciton binding energy (320 meV) to be mostly independent of interlayer distance.…”
Section: Interlayer Spacingmentioning
confidence: 99%